Analisis Inovasi Pelayanan Akta Kelahiran Online : (Studi Kasus Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Tana Toraja) - Karua, Gusriani Arrang; Matasik, Ade Lisa (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2022)
This study aims to determine whether the Online Birth Certificate Service Innovation at the Departement of Population and Civil Registration of Tana Toraja Regency has been running well. The benefit of this research is that it can contribute ideas, information for the Partement of Population and Civil Registration of Tana Toraja Regency to improve service in the implementation of making online birth certificates. This research was conducted using qualitative methods with data collection techniques namely interviews, observation, and documentation. Data analysis shows that the birth certificate service innovation that is being carried out is service innovation in a new way in interacting whit the community whit birth certificate registration service through WhatsApp media sending complete files or requirements for making birth certificate to the Population and Civil Registration Office of Tana Toraja Regency. Although the public does not understand about making birth certificates online, most of the people participate in the online birth certificate service program which is implemented at the Office of Population and Civil Registration of Tana Toraja Regency